Evaluation of smart city construction efficiency based on multivariate data fusion: A perspective from China - Mao, Chao; Wang, Zhuoqi; Yue, Aobo; Liu, Huan; Peng, Wuxue (Ecological indicators, 2023)
•More than five data sources were used in the evaluation.•Extending evaluation data sources through data mining, text mining and other methods.•Evaluation choices with government and public as core evaluation subjects.•The SE-SBM-undesirable model and Malmquist index were applied for evaluation.•The results provide a comprehensive picture of smart city construction efficiency. In the face of urban development challenges brought about by high-speed urbanization, smart cities have been recognized as a necessary way to promote the modernization of urban governance systems and governance capacity. Therefore, the establishment of a scientific and comprehensive evaluation index system is crucial to the sustainable construction of smart cities. Based on existing research, this study innovatively uses multivariate data to construct an evaluation index system for the construction level of smart cities, and then systematically evaluates the smart city construction efficiency of 37 cities from 2016 to 2021 using the Super-efficiency slack-based model considering undesired output and the Malmquist index. Finally, measures are proposed to promote the orderly and healthy development of smart cities by combining domestic and international experience in smart city construction and policy recommendations. Results show the following: (1) Overall, the imbalance in the efficiency of China’s smart city construction between regions has improved, but a gap remains in the central and western regions in comparison with the east. (2) The improvement in smart city construction efficiency correlates with regional economic development, showing a gradual decrease from east to west. (3) The evaluation results can provide theoretical support and a decision-making basis for relevant government departments to optimize smart city development planning and scientifically formulate smart city development policies.